A Content Analysis Of The #BumiAwetMuda Campaign Owned By Perusahaan Listrik Negara (PLN) On The @kompascom TikTok: - - Santoso, Michelle Celine (Jogjakarta Communication Conference (JCC), 2024)
Indonesia currently needs a new renewable energy transition to achieve the Net Zero Emission (NZE) program. The Perusahaan Listrik Negara (PLN) is collaborating with Kompas.com to invite people to switch to electric power, especially in the use of electric vehicles through the #BumiAwetMuda campaign on TikTok social media. This research is qualitative research using content analysis methods, with data collection techniques applied through documentation. The research objects used by researchers are four contents of the #BumiAwetMuda campaign on the TikTok account @kompascom, categorized by activities involving electric vehicles. The results of this research show that the content of the electrifying lifestyle message in the #BumiAwetMuda campaign in the knowledge category about electric vehicles contains messages about the positive impact of increasing accessibility, comfort, and support for renewable energy.